Africa needs one voice - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Kiwa Matsimbe, researcher at NEPAD Regional Fish Node: " Africa needs one common strategy on Agricultural Researcher" The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/